2023
DOI: 10.1186/s12905-023-02400-5
|View full text |Cite
|
Sign up to set email alerts
|

The risk of sexual dysfunction associated with alcohol consumption in women: a systematic review and meta-analysis

Abstract: Background Alcohol abuse among women is a significant health problem. Consuming alcohol in high amounts causes decreased sexual stimulation, vaginal lubrication, dyspareunia, and difficulty reaching orgasm. Due to the different effects of alcohol consumption on sexual function, this study aimed to investigate the effect of alcohol consumption on sexual dysfunction in women. Methods In this study, the researchers conducted a systematic search of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Previous studies have demonstrated a significant correlation between drinking and increased risk of sexual dysfunction in male or female patients. 14 , 15 Alcohol consumption can induce a reduction in testosterone levels by inhibiting its synthesis, which affects libido and sexual potency. 16 These studies have shown that alcohol is a depressant that impairs sensory nerve input, resulting in decreased libido, arousal, and intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a significant correlation between drinking and increased risk of sexual dysfunction in male or female patients. 14 , 15 Alcohol consumption can induce a reduction in testosterone levels by inhibiting its synthesis, which affects libido and sexual potency. 16 These studies have shown that alcohol is a depressant that impairs sensory nerve input, resulting in decreased libido, arousal, and intensity.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that an increased risk of sexual dysfunction in the elderly who have history of alcohol consumption and depression. Previous studies have demonstrated a signi cant correlation between drinking and increase risk of sexual dysfunction [17][18]. And depression is common in the elderly 19], most studies showed that depression is a risk factor for sexual dysfunction and its relation -ship should be viewed as two-way [20].…”
Section: Discussionmentioning
confidence: 99%
“…The selected confounders are shown to be associated both with sexual function and cardiovascular health. 3 , 7 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 Age was reported in years. Relationship happiness was evaluated with the question “How do you consider your current relationship?” and with answer options “very happy”, “fairly happy”, “neither happy nor unhappy”, “fairly unhappy”, and “very unhappy” and dichotomized as happy/unhappy.…”
Section: Methodsmentioning
confidence: 99%